Implication of vascular endothelium and interleukin-22 in rejection of cardiac allografts - Kapessidou, Panayota (Universite Libre de Bruxelles, 2010)
Cardiac transplantation is governed by complex immunological mechanisms contributing to different types of allograft rejection. Early non-specific graft failure and chronic rejection (cardiac allograft vasculopathy) represent the main limitations for the recipients’ short- and long-term survival respectively. To date, the pathogenesis of both rejection types remains ill-defined. However, it is believed that they are related to an immunologically mediated potent inflammatory process, occurring whether early after transplantation (acute), or lasting for the lifetime of the graft (chronic). The initiating mechanisms of chronic rejection in solid organ transplantation remain ill-defined. Emerging evidence sustains that graft vasculopathy is primarily driven by alloreactive CD4+ T lymphocytes sensitized by the indirect pathway of allorecognition. To date, whereas the nature of APCs involved in this particular pathway has yet to be identified, it appears challenging to speculate that recipient-derived endothelial cells (ECs) repopulating the graft may represent the main cell targets recognized by indirectly primed alloreactive CD4+ T cells to mediate the rejection of cardiac transplants. In the first part of this thesis, we specifically studied the indirect pathway of allorecognition with a transgenic mice (Marilyn mice) model that expresses a T cell receptor (TCR) transgene which recognizes the male antigen H-Y in an I-Ab-restricted fashion. Our results provide evidence that graft endothelium replacement by recipient-type cells expressing MHC Class II molecules is required for the chronic rejection of vascularized cardiac transplants mediated by indirect pathway alloreactive CD4+ T cells. The purpose of the second part of the thesis was to investigate the potential implication of interleukin-22 (IL-22), an early phase secreted proinflammatory cytokine of the IL-10 family, in the acute rejection of cardiac allografts. IL-22 was recently described as an effector key modulator of the inflammatory process produced mainly by differentiated CD4+ T cells of the Th17 lineage. As being closely related to IL-10 and IL-17, both involved in the rejection process of vascularized heart allografts, we attempted to determine the precise role of IL-22 in this process. Experiments were conducted with a recently developed murine model deficient for the IL-22 gene (IL-22KO). The results of the second part of the thesis show that IL-22 is not an effector cytokine in cardiac allograft rejection. In contrast, as being early expressed into the allograft, likely IL-22 plays a protective role in the inflammation leading to acute cardiac rejection, probably depending on a neutrophil-related mechanism. In conjunction with current understanding of inflammatory and antigen-specific events in allografts, overall, our results provide new insights into the mechanisms of chronic and acute cardiac rejection, thus prompting to further interrogations and appealing novel therapeutic strategies. Pharmacologic manipulation of endothelium is challenging. Given their capacity to sense and rapidly respond to the local environment, ECs are the ideal targets for rapid systemic delivery of therapeutic agents. Combination therapy is required to reduce inflammatory reaction and endothelial activation, to modulate endothelial dysfunction and promote endothelial survival. Also, given that IL-22 may alleviate tissue destruction during inflammatory responses, therapies that enhance its production and protective action in the transplanted organs seem attractive to specifically affect tissue responses, without exerting direct effects on the immune response. === Doctorat en Sciences médicales === info:eu-repo/semantics/nonPublished